Assessing the Impacts of Child Labor on the Children of Uganda a Case Study of Kisenyi, Katwe, Bwaise and Mbale - Aisha Nalumansi (Uganda Christian University, 2024)
The Research focuses on Katwe, Bwaise, Kisenyi, and Mbale because these are areas with the highest number of child laborers, the majority of whom work on streets, quarries, and agricultural sectors. The main objective of this study was to assess the impacts of child labor on the children of Uganda with particular aims of investigating the origins of child labor, assessing the impacts of child labor and analyzing the legislative framework against child labor. The study investigates the causes and effects of child labor, as well as the problems that children encounter at work, using current literature and legal precedents. The study is based mostly on desk review of various information sources from Uganda and other countries to draw relevance and a qualitative data collection was used to obtain data. The findings reveal that, there are several causes of child labor including, poverty, limited access to education, High population growth, orphan hood, unemployment and so on. According to the study, parents participate in forcing their children into labor, despite the fact that some believe they are teaching their children life skills that would benefit them in adulthood. Child labor has a number of negative consequences, including muscle strain and skeletal damage, malnutrition and stunted growth, exposure to hazardous chemicals, fatal accidents, emotional distress, and trauma, among others. The findings also reveal that, despite Uganda being a signatory to a number of international laws, child labor continues to exist, owing to the inadequate implementation and enforcement of these laws. It is also established that children between the ages of 5 and 17 are the most exploited, with a high number of boys physically participating in employment than girls. The study recommends that the government should consider increasing the minimum legal age for children to work to at least an age where they are self-aware and can protect themselves from the dangers of work. The government should enact strict legislation that will be successfully executed to completely eradicate child labor. The government should also educate the public about the dangers and consequences of child labor by informing parents that children who attend school have a brighter tomorrow than those who work at a young age. In order to allow low-income families to send their children to school, public schools should be made more accessible to all children. Additionally, rigorous policies should be enacted to prevent school public schools from hiking school dues because this makes it so hard for poor families to take their children to school hence initiating them to labor.